Longarm and the Whiskey Creek widow - Evans, Tabor (New York Jove Books, 1998)
Longarm must make a choice - chase down wanted men, or fall for a beautiful lady.
Keywords: Longarm (Fictitious character) -- Fiction. -- Longarm (Fictitious character)